CRITICISM OF DARWIN’S THEORY OF EVOLUTION BY MUSLIM SCHOLARS - Ibrahim, Abdul Halim; Baharuddin, Madiha (Online Journal of Research in Islamic Studies, 2017)
The Theory of Evolution is a major principle of modern biology. The theory was initiated by Charles Darwin in 1859, and has been criticized from various aspects by scholars from the West and the East. The principle of this theory is based on materialism and this ideology also influenced some Muslims’ thought. At the same time, it could also affect the social belief system of Muslims. This article will briefly review the background of Darwin’s Theory of Evolution, and analyze major criticisms of the theory by Muslim scholars from the religious, scientific, and philosophical perspectives. This article will highlight the main issues in the criticisms of Muslims scholars on the Theory of Evolution, and discuss the weaknesses of the theory from the point of view of Muslim scholars. The method used in this paper is primarily qualitative, with the data and arguments obtained from textual analysis.